Sets in the tool environment for developing program modules - Kovalev, A.D.; Nikitin, S.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2000)
Some classes of sets used for constructing the tools to support dynamical tree-type and network structures of data are considered. A number of methods for representation of sets and operations on them are given. Examples illustrating manipulations with unpacked and packed lists of elements as well as with unpacked bit scales are discussed.